Jurnal Penelitian / Artikel Ilmi Motivasi Penggunaan Kosmetika Perawatan (Skincare) di Kalangan Mahasiswa: Studi pada Mahasiswa Fakultas Teknik Universitas Negeri Surabaya - Septiawardani, Dea; Usodoningtyas, Sri; Faidah, Mutimmatul; Dwiyanti, Sri (Jurnal Tata Rias, 2025)
From observation activities at Surabaya State University, it was discovered that students used more skincare cosmetics for every facial problem they each experienced, this had an effect on student motivation. This research aims to examine the use of skincare cosmetics on student motivation. The approach used is descriptive with quantitative methods. The population in this study were students from the 2022 class of PKK class with a sample of students who had glowing or problematic facial skin, the sample taken was 30% of the total number. The research instrument is a questionnaire instrument with data analysis using percentages and one sample t-test. The research results showed that students' motivation towards using skincare cosmetics using a questionnaire distributed via gform showed an average of 73.66% with the good category consisting of topics: encouragement of the need to own the product, encouragement of the need to use the product, encouragement to support appearance, encouragement to trends in the social environment and encouragement of product craze.